2010
DOI: 10.1016/j.gie.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing colorectal cancer risk despite surveillance colonoscopy: the Polyp Prevention Trial Continued Follow-up Study

Abstract: Background Despite regular colonoscopy, interval colorectal cancer (CRC) may occur. Long-term studies examining CRC rates in patients with previous colonoscopy are lacking. Objective We examined the rate of interval CRC in the Polyp Prevention Trial-Continued Follow-up Study (PPT-CFS), an observational study of participants which began after the Polyp Prevention Trial (PPT) ended. Design Prospective Setting A national U.S. community-based polyp prevention trial Main Outcome Measurements Medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 30 publications
6
73
0
4
Order By: Relevance
“…Several studies evaluating interval CRCs found that these cancers can be attributed to incomplete polypectomy in about 10% to 30% of cases 13,20,22,64,65 . Since ADR is essentially geared at assessing detection and not resection, the inadequate quality in these cases would not be reflected by measuring the ADR.…”
Section: Incomplete Adenoma Resectionmentioning
confidence: 99%
“…Several studies evaluating interval CRCs found that these cancers can be attributed to incomplete polypectomy in about 10% to 30% of cases 13,20,22,64,65 . Since ADR is essentially geared at assessing detection and not resection, the inadequate quality in these cases would not be reflected by measuring the ADR.…”
Section: Incomplete Adenoma Resectionmentioning
confidence: 99%
“…Leung and colleagues studied colorectal cancer risk despite surveilance colonoscopy and concluded that despite frequent colonoscopy there was a persistent ongoing risk of cancer in the years after the trial. Subjects with a history of advanced adenoma are at increased risk of subsequent cancer and should be followed closely with continued surveillance (Leung et al, 2010). Importantly, the performance of annual colonoscopy has not been shown to improve fiveyear survival.…”
Section: Endoscopic Techniquesmentioning
confidence: 99%
“…Lower rates are likely to be explained by poor examination quality. Some incidental CRC's are probably related to missed adenomas (15,47). However, complete resection of early CRC by an experienced endoscopist is possible, making polypectomy curative.…”
Section: Existing Guidelines For Quality Assurance (Asge)mentioning
confidence: 99%
“…Protocols for routine monitoring of interval cancers are being developed (46). A proportion of interval cancers occur due to aggressive tumour biology (17), but missed lesions and incomplete polyp removal are important contributing factors (15,16).…”
Section: Interval Cancers It Is Anticipated By the National Health Smentioning
confidence: 99%
See 1 more Smart Citation